THE IMPLEMENTATION OF ACCOUNTANCY INFORMATION SYSTEM OF MABRUR SAVINGS PRODUCT AT BANK SYARIAH MANDIRI AT BOGOR BRANCH OFFICE - MUHAMMAD NUR RIZQI (The Accounting Journal of Binaniaga, 2017)
Pirgrimage (Haj’s) saving is one of common banking products. Mabrur pilgrim saving is one of the products of Bank Syariah Mandiri. Bank Syariah Mandiri has been operating this system for more than 10 years. The Accountancy Information System is an integrated system required and one of the samples is SISKOHAT. This research is discussing about the registration procedure and the payment procedure regarding regular pilgrim at Bank Syariah Mandiri which have been identified on the related flowchart. In general those two procedures have been applied properly and have become a reliable accountancy information system to prepare a financial report accordingly.Keywords : SIA, Saving Product Mabrur BSM.